PENYADARTAHUAN MASYARAKAT TERHADAP PERAN EKOLOGIS AKAR BAHAR SEBAGAI UPAYA PERLINDUNGAN EKOSISTEM TERUMBU KARANG BERBASIS MASYARAKAT DI TAMAN NASIONAL KARIMUNJAWA - Aulia Seto Sandhi Sanova; Aditano Yani Retawimbi; Angka` Mahardini; Mualim Tahar; Muhammad Najwan Kamil; Muhammad Yusuf; Nenik Kholilah (Universitas Mataram, 2026)
The success of coral reef ecosystem conservation depends heavily on the active participation of local communities as key stakeholders. Black coral is crucial for providing habitat for numerous marine species, but is vulnerable to human exploitation due to its slow growth. Although Indonesia has legal protection for black coral, its commercialization as a souvenir continues unchecked in Karimunjawa National Park, primarily due to low public awareness. This community service activity aimed to increase understanding of black coral ecology, its vulnerability, and population status, while also fostering dialogue among community members to promote conservation adherence. The approach used included field surveys, stakeholder coordination, oral presentations, and focus group discussions (FGDs) with 15 participants from diverse backgrounds in Karimunjawa. The program's effectiveness was assessed through pre- and post-tests, demonstrating a significant increase in knowledge—from 57% correct answers initially to 92% after the intervention. Participants also expressed their hopes for addressing conservation issues in their communities. Overall, targeted education proved effective in raising awareness, laying the foundation for community-led ecosystem protection. This deeper understanding is expected to strengthen future marine conservation efforts.